ASSESSMENT OF ANTIOXIDANT DEFENCE SYSTEM AS A SELECTION CRITERION AGAINST TO OXIDATIVE STRESS DURING THE EARLY GROWTH PERIOD OF COMMON WHEAT - Alpay Balkan; Sefer Demirbas (Journal of Animal and Plant Sciences, 2024)
Plants are negatively impacted by high levels of reactive oxygen species (ROS). The objective of the study was to find out the effect of exogenous hydrogen peroxide (H2O2) induced oxidative stress on the antioxidant defence system of common wheat seedlings and to screen the genotypes for tolerance or susceptibility to stress. In this study, three varieties (Flamura-85, Selimiye, and Esperia) and three advanced lines (TDE-45-1, TDE-84-5, and TDE-111-9) were used as experimental materials. The experiment was conducted in accordance with a randomized split-plot design with three replicates. In the experiment, wheat genotypes were allocated to the main plots, and different H2O2 applications (0-control, 50, 100 mM) were applied to the subplots. Wheat plants grown in pots were irrigated with different H2O2 solutions to induce oxidative stress at the two- to three-leaf stage. One week after application, the antioxidant enzyme levels, thiobarbituric acid reactive substance (TBARS) content, H2O2 content, plant growth and leaf water status of the seedlings were examined. The differences between the means of the wheat genotypes were statistically significant for all studied traits. The results indicated that the response of common wheat genotypes to oxidative stress differed. Flamura-85 and TDE-45-1 were identified as the genotypes with the best antioxidant defence system against H2O2. The resistance of wheat to oxidative stress may be improved by using these genotypes as novel genetic resources. In addition, biochemical analysis results indicated that superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), TBARS and H2O2 could be used as selection parameters in future wheat breeding studies to screen the resistance of wheat genotypes to oxidative stress during the early growth period.
Keywords: Oxygen radicals; Triticum aestivum; hydrogen peroxide; oxidative stress; shoot dry weight